Penilaian Kinerja Pemasok Menggunakan Metode Vendor Performance Indicator dan Fuzzy Analytical Hierarchy Process (FAHP) - Syifa, Saidatus; Nurhasanah, Nunung (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
PT. Agripratama Mitra Sejahtera, a company with the nickname Sobat Veggies (SV), buys and sells more than 100 types of vegetables, fruit, meat and other related products. SV buys from farmers and other companies with different prices and product quality, therefore SV needs to evaluate these suppliers for cost efficiency. The analytical methods used by SV to help in making the right buying decisions are the Vendor Performance Indicator (VPI), followed by the Fuzzy Analytical Hierarchy Process (FAHP). Performance appraisal is carried out on selected vegetable commodity suppliers because they have high sales levels. The VPI method is used with the concept of QCDFR (Quality, Cost, Delivery, Flexibility, Responsiveness) with a total of 13 sub-criteria. The method gives 5 best vegetable suppliers namely CV. Madani Creative Business, Depari Group, CV. Mizan, Central Market, and Quality Fresh Organic. Following through using the FAHP method, we get the ranking as follows: (1) CV. Madani Creative Business with a value of 0.50, (2) the Central Market with a value of 0.48, (3) Quality Fresh Organic with a value of 0.46, (4) Depari Group with a value of 0.44 and (5) CV. Mizan with a value of 0.41. Keywords - Supplier Performance Assessment, VPI, FAHP, QCDFR